MANAJEMEN STRATEGI IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA RAHMATAN LIL ALAMIN DI MAN 1 BANDAR LAMPUNG - Marlisa, Marlisa; Amiruddin, Amiruddin; Ayu, Sovia Mas (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This study focuses on the management strategy for implementing the Project to Strengthen the Profile of Pancasila Students and Rahmatan Lil Alamin (P5RA) at MAN 1 Bandar Lampung. The purpose of this research is to analyze the strategies, approaches, and challenges in the implementation of P5RA in order to improve students' character, skills, and understanding of Pancasila values. A qualitative research method was applied, utilizing data collection techniques such as observation, interviews, and documentation. The findings reveal that the P5RA project is effectively integrated into various learning activities, including co-curricular, integrated, and extracurricular activities, contributing to the holistic development of students. However, challenges related to external partnerships and resource availability were identified. The involvement of both internal and external stakeholders, such as teachers, students, and the local community, played a crucial role in the success of the project. The study recommends enhancing external partnerships and improving infrastructure to sustain and develop the project further. The results indicate that the implementation of P5RA has a positive impact on the formation of students' character and practical skills, aligning with the goals of national education.